InAlN/GaN HEMTs on Si With High fT of 250 GHz - Xing, Weichuan (2020)
In this letter, InAlN/GaN high electron mobility transistors (HEMTs) with 40-200 nm rectangular gates and 300-700 nm source-to-drain distances were fabricated on Si substrates. The device with 40-nm gate and 300-nm source-to-drain distance exhibited a high drain current of 2.66 A/mm, a transconductance (gm) of 438 mS/mm, and a high current gain cutoff frequency (fT) of 250 GHz. To the best of our knowledge, this is the highest fT value reported so far for GaN-based transistors on Si. An effective electron velocity of 1.1 × 107cm/s was extracted, which is comparable with those reported for InAlN/GaN HEMTs on SiC. These excellent results indicate that GaN HEMTs on Si have a great potential for low-cost emerging mm-Wave applications.